Implementation of Accrual-Based Government Accounting Standards in the Village Government of Dompu District - Safiratun Hasanah; Irwansyah Irwansyah; Sumarni Sumarni (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the implementation of the accrual-based government accounting system at the village government level, especially in Dompu District, Dompu Regency. The method used in this study is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The informants selected were village government financial management officials who had direct knowledge of the accounting practices applied. The results of the study indicate that although financial management officials in Dompu District did not fully understand the definition of accrual-based accounting, they had implemented several basic principles of the system in financial recording. The implementation of the accrual-based accounting system in these villages experienced challenges, especially related to the separation between budget accounting and financial accounting, as well as a lack of understanding of the complexity of the resulting financial reports. Nevertheless, most villages in Dompu District have recognized changes in equity and long-term liabilities in accordance with the accrual principle, although there are still obstacles in budget management that affect recording. This study provides insight into the challenges and implementation of the accrual-based accounting system at the village government level, as well as the importance of training and a deeper understanding of accrual-based accounting at the local level.